Respuesta :
Answer:
A.) 1644
given equation: [tex]\sf p(x)=x^4-9x^3-5x^2-3x+4[/tex]
To be divided with ( x + 5 )
Then,
x + 5 = 0
x = -5
Put this into the equation to find the remainder.
[tex]\sf p(x)=(-5)^4-9(-5)^3-5(-5)^2-3(-5)+4[/tex]
[tex]\sf p(x)= 1644[/tex]
Use the remainder theorem to find the remainder when p(x)=x^4-9x^3-5x^2-3x+4 is divided by x+5
A.) 1644
B.) 1244
C.) -636
D.) -644
~~~~~~~~~~~~~~~~~~~~~
[tex]\sf p(x)=x^4-9x^3-5x^2-3x+4[/tex]
[tex] \sf p(x) = (-5)^4 - 9(-5)^3 (-5)^2 - 3 (-5) + 4 [/tex]
[tex] \sf \green {(p(x) = 1644)} [/tex]
#CarryOnLearning
#LibreAngMatuto